Neurological autoimmune disorders with prominent gastrointestinal manifestations: A review of presentation, evaluation, and treatment. Issue 10 (23rd April 2019) - Blackburn, Kyle M.; Kubiliun, Maddie; Harris, Samar; Vernino, Steven
Abstract: Background: The identification of autoantibodies directed against neuronal antigens has led to the recognition of a wide spectrum of neurological autoimmune disorders (NAD). With timely recognition and treatment, many patients with NAD see rapid improvement. Symptoms associated with NAD can be diverse and are determined by the regions of the nervous system affected. In addition to neurological symptoms, a number of these disorders present with prominent gastrointestinal (GI) manifestations such as nausea, diarrhea, weight loss, and gastroparesis prompting an initial evaluation by gastroenterologists. Purpose: This review provides a general overview of autoantibodies within the nervous system, focusing on three scenarios in which nervous system autoimmunity may initially present with gut symptoms. A general approach to evaluation and treatment, including antibody testing, will be reviewed. Abstract : Autoimmune disorders of the nervous system can cause severe gastrointestinal manifestations (vomiting, weight loss, and gastroparesis) in the absence of other signs of neurological dysfunction and may initially be evaluated by gastroenterologists prior to the onset of clear neurological dysfunction. This review aims to familiarize gastroenterologists with the evaluation and treatment of three neurological autoimmune disorders that have prominent gastrointestinal symptoms.